2022
DOI: 10.1038/s41598-022-23021-2
|View full text |Cite
|
Sign up to set email alerts
|

A dual-view multi-resolution laparoscope for safer and more efficient minimally invasive surgery

Abstract: Minimally invasive surgery (MIS) is limited in safety and efficiency by the hand-held nature and narrow fields of view of traditional laparoscopes. A multi-resolution foveated laparoscope (MRFL) was invented to address these concerns. The MRFL is a stationary dual-view imaging device with optical panning and zooming capabilities. It is designed to simultaneously capture and display a zoomed view and supplemental wide view of the surgical field. Optical zooming and panning capabilities facilitate repositioning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…1,8 Notably, in our experience with this case, we found that laparoscopic management of elemental mercury sequestration in the appendix has several advantages over open surgery: 1) Laparoscopic surgery is minimally invasive, which means that it involves smaller incisions and less tissue damage compared with open surgery. This can result in less pain, shorter hospital stay, and faster recovery time for the patient; 2) Laparoscopic surgery provides better visualization of the surgical field, 14 which can help the surgeon identify and remove all of the mercury-contaminated tissue more effectively. This can reduce the risk of leaving mercury behind, which could lead to further complications; and 3) Laparoscopic surgery is associated with a lower risk of infection and other postoperative complications, such as bleeding and hernia formation.…”
Section: Discussionmentioning
confidence: 99%
“…1,8 Notably, in our experience with this case, we found that laparoscopic management of elemental mercury sequestration in the appendix has several advantages over open surgery: 1) Laparoscopic surgery is minimally invasive, which means that it involves smaller incisions and less tissue damage compared with open surgery. This can result in less pain, shorter hospital stay, and faster recovery time for the patient; 2) Laparoscopic surgery provides better visualization of the surgical field, 14 which can help the surgeon identify and remove all of the mercury-contaminated tissue more effectively. This can reduce the risk of leaving mercury behind, which could lead to further complications; and 3) Laparoscopic surgery is associated with a lower risk of infection and other postoperative complications, such as bleeding and hernia formation.…”
Section: Discussionmentioning
confidence: 99%